DO TEACHING HOSPITALS HAVE COMPARABLE OUTCOMES TO NON-TEACHING HOSPITALS FOR PERCUTANEOUS CORONARY INTERVENTIONS? - MUNJAL AMIT; PRACHI ARUN; BANSAL CB; KUMARI SNEH; SHARMA ANJALI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Teaching hospitals may have comparable surgical outcomes as compare to non-teaching hospitals from major surgical conditions. However, limited data are available regarding percutaneous coronary interventions performed in teaching hospitals involving trainées. Methods: In this observational study, 103 patients who had percutaneous coronary intervention (PCI) in a hospital attached to a medical college were retrospectively evaluated. The indications for PCI were ST-elevation myocardial infarction (STEMI), improvement in quality of life in patients with atypical chest pain, angina (stable and unstable, a positive stress test, or non-STEMI, and patients without any documented angina, chest pain, or positive stress test. Teaching hospital status was as defined by the National Medical Commission-based number of teaching faculty/trainees to-bed ratio. Trainee participation in at least 50% PCI procedures in the teaching hospital was a pre-requisite for inclusion in the study. Results: The mean age of participants was 60.4±9.8 years; there was a male preponderance (84.4%). Prior PCI was done in 11.3% patients and 7.5% had history of stroke previously. About 20.6% were diabetics, 33.9% had dyslipidemia, and 50.9% had systemic hypertension, respectively. Left anterior descending with the left coronary circumflex artery was the most affected vessels in both sexes combined and 84.4% patients had double-vessel disease. Thirty-one (31.9%) underwent PCI by femoral route and 72 (68%) by radial route, respectively. PCI was successful in 74 (71.8%) and 10 (9.7%) had vascular complication. The mortality rate was 6 (5.8%). Twenty-five (24.3%) patients had reinfarction. Conclusion: Although vascular complications may occur at the hands of trainees, the overall mortality rates are low for PCI in teaching hospitals.